SISTEM INFORMASI SIMPAN PINJAM KOPERASI SYARIAH BAITURRAHMAN BOJONG GEDE BERBASIS WEBSITE - Azzindan Zulvan (2023)
Cooperatives are individual legal entities, which are very beneficial for the surrounding community. Sharia cooperatives are a type of cooperative practice based on the principles of Islamic religious law or better known as shari'ah. The difference between conventional and Sharia cooperatives lies in the rules that are applied, the most striking thing is that Sharia cooperatives use contracts in every transaction process, while conventional ones do not. Sharia cooperatives are indeed no more popular than conventional cooperatives, but if you see the potential that exists in Indonesia with the largest Muslim majority in the world, Sharia cooperatives need to be developed. KKS Bairuttahman Bojong Gede is one of the sharia cooperatives in Bogor Regency and the only cooperative in Bojong Gede. Technology is very much needed in terms of system development in cooperatives, Baiturrahman Bojong Gede KKS is one of the Sharia principled cooperatives that needs development because the operating system still uses the old system, namely Microsoft Excel which is at risk for the data. A website-based application system is present and can help provide solutions for cooperative operations, storing and managing data will be more secure and efficient. The system design method used is the waterfall and the PIECES analysis method. The PIECES analysis method is used to identify existing problems related to performance, economy, security, efficiency, and service. The programming language for website creation uses PHP and HTML with a MySQL database. The conclusion obtained from the results of this study is that Islamic cooperatives are business assets that need to be developed because they bring many benefits to the surrounding community, with system development carried out on the use of technology. And the goal is that the development of this system is expected to make it easier for the Baiturrahman Bojong Gede PSC to better manage its data and operations. Keywords: Cooperative, Sharia, Information System, Website